Israel : Selected Issues Paper. (IMF Staff Country Reports; Country Report ;, 2012)
This Selected Issues Paper states that Israel's growth performance is impressive, with real GDP growing at a faster pace than many other OECD countries. The secular Jewish population enjoys a high level of living standards, whereas most Arab and Haredi people are poor, with poverty incidence reaching 60 percent for both groups. Low employment in Arab and Haredi communities is mainly accounted for by the low employment rate of Arab women and Haredi men.